Alat Bantu Pedoman Ibadah Umat Islam Melalui Aplikasi Zipedia Berbasis Mobile - Yaya Sudarya Triana; Hendri Gunawan; Dwi Prasetyo; Krisna Pangestu (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
It's very rare to find people who can easily read the Koran, dhikr and give alms especially for workers. Busy activity makes them feel difficult to do religious activities, especially if they have to carry the holy book Al-Quran and Tasbih. along with these problems the presence of technology is very much needed as an alternative to the holy book of the Koran to uphold the community in carrying out their worship activities in their preoccupations. Therefore, in the current research an application will be made as a Tool and Guidance for Islamic Worship, an application that can help the community more easily in conducting worship activities reading Al-Quran and Dhikr. This application uses the RAD (Rapid Application Development) method. From the results of this study produce a Zipedia application by implementing a Rapid Application development method, the conclusion that with the Rapid Application development method can produce Islamic applications that can facilitate the community in worshiping, the conclusion that with the RAD method in conducting worship.